Малощетинковые черви, обитающие на речных раках некоторых водоемов Украины. Сообщение I. Branchiobdellidae - Бошко, Е.Г. (Вестник зоологии, 1983)
Three species of the Branchiobdella genus are found in crayfishes from water bodies in the Ukraine: B. kozarovi Subchev, 1978 — in Astacus leplodactylus Esch. from the Duieper, South Bug and Danube basins; B. penfodonfa Whitman, 1882 and B. balcanica Moszynski, 1937 — in Asfacus astacus L. Original descriptions and photos of these species are presented with a degree of crayfish aifection with Branchiobdella. An identification key is compiled for delermining European species of the Branchiobdella genus.